Electromagnetic power of lightning superbolts from Earth to space - J.-F. Ripoll (Nature Portfolio, 2021)
Superbolts are powerful, rare lightning events. Here, the authors show simultaneous satellite and ground measurements of a superbolt, and demonstrate different properties of superbolts and lightnings.